Management of Student Potential Development at A Character School with Talent-Friendly Approach Based on Local Wisdom Through UMKM Internship Program - Rahma, Lailatul (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study discusses the management of student potential development in a talent-friendly character school, focusing on the application of local wisdom through the Micro, Small, and Medium Enterprises (UMKM) internship program. The aim of this development is to nurture the individual potential of students, both academically and non-academically, through an approach that values their talents and interests. A local wisdom-based approach is employed to preserve cultural identity, strengthen character, and instill values relevant to the students' social environment. The UMKM internship program is implemented as a means of developing practical skills and entrepreneurship among students, with the goal of connecting school learning with the real-world workforce. This internship not only equips students with practical knowledge but also provides direct experience on how local wisdom can be integrated into economic activities.The research method used is qualitative, with data collection methods including in-depth interviews and observations. The study concludes that a talent-based and local wisdom-based approach, complemented by the UMKM internship program, can enhance students' skills, confidence, and readiness to face future challenges, both academically and professionally.